Historiography and identity III: Carolingian approaches (2021)
Historiography and identity III: Carolingian Approaches is the third volume of a series of six, which aims to study the relationship between the writing of history and the construction of identity from antiquity to the Middle Ages. Taken together, these volumes hope to recover the potential that historiography developed to articulate and shape strategies of identification in the ancient, late ancient, and medieval worlds. The third volume explores this history in Carolingian Europe from the 8th to the 10th century, which was crucial time for the definition of the cultural landscape of Latin Europe in the Middle Ages.